Exploring an adaptability approach: how creative return processors impact firm performance. Issue 3 (4th March 2021) - Espinosa, Jennifer A.; Stock, James; Ortinau, David J.; Monahan, Lisa
Abstract : Purpose: The authors explore complex adaptive systems (CAS) theory as an updated theoretical perspective for managing product returns that better matches the chaotic nature of recent consumer behaviors. CAS theory highlights the importance of agents who create and self-organize to help systems adapt in unpredictable environments. Design/methodology/approach: This research utilizes data collected from return managers in an online survey and applies regression analyses to estimate the influence of the focal variables. Findings: Empirical evidence of the firm flexibility–firm adaptability link is established, and return processor creativity positively relates to this link. The firm flexibility–firm adaptability link fully mediates the relationship between return processor creativity and returns management performance and partially mediates the relationship between return processor creativity and relationship quality. Nonmediated effects were observed for turnover and revenue size. Practical implications: Managers of returns who embrace an adaptability approach become facilitators of returns by supporting processor creativity. Enhancing the autonomy of processors in their day-to-day work increases the knowledge-creation capabilities of the firm, which helps the firm move forward and adapt in an uncertain environment. Originality/value: This research presents empirical evidence of the underlying mechanisms of CAS theory in the product returns context by studying processor agents and argues that CAS theory better fits the current dynamics of the product returns environment. Further, this paper extends work by Espinosa et al. (2019) and Nilsson (2019) by studying how a specific human characteristic – creativity – impacts product returns management.